Identification of genetic diversity of jarak pagar (jatropha curcas l.) in central java based on isoenzyme marker - AHMAD YUNUS (Biodiversitas Journal of Biological Diversity, 2007)
Jatropha curcas is one of the plant which produces the renewable fuel. At the present time, the problems of the jatropha are litle information about genetic information included genetic diversity on inter species at Central Java and even in Indonesia. The diversity of inter species can be known by isozyme traits, this marker provide clustering species. The objective of this research were to identify jatropha based onisozyme markers. This research was conducted on Mei until December 2006. The samples were obtained from Banyumas, Pati, Cilacap, Pemalang, Jepara, Kudus, Batang and Grobogan. Isozyme analysis was conducted on Central Laboratory, Sebelas Maret University. Analysis of isozyme were conducted with isozyme Alcohol dehydrogenase (ADH), Sorbitol dehydrogenase (SOD), Schimimate dehydrogenase (SHD) and Isocitrate dehydrogenase (IDH). Analysis of data used the metode of Cluster Metode Average Linkage withDICE coefficienct. The conclusion of this research were: based on analysis of enzyme sorbitol dehydrogenase (SOD) and schimimate dehydrogenase (SHD), spesies from Kudus I was different with other species, while based on Alcohol dehydrogenase (ADH) and Isocitrate dehydrogenase (IDH) showed that species from Grobogan has genetic similarity with Kudus I.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Jatropha curcas, Isoenzim